Analysis of Accountability, Transparency, and Service Quality in Muzakki Trust Zakat Management Organization - Fatmasari, Dewi; Dinningthias, Desih; Sukardi, Didi; Ulfah, Mariyah; Ravindran, Kirutikha (Institut Agama Islam Negeri Kendari, 2024)
This research is motivated by the existence of a gap between Muzakki's beliefs and zakat management organizations. This study aims to find out how to analyze accountability, transparency, and quality of service on Muzakki's trust in zakat management organizations at Baznas, Indramayu Regency. Collecting data by distributing questionnaires on muzakki's trust in Bazna, the sampling technique used is non-probability sampling with accidental sampling. This study uses a descriptive verification method, and the analytical method uses multiple regression analysis. This study shows that accountability has a positive and significant effect on muzakki's trust, transparency has a positive and significant effect on muzakki's trust, also service quality has a positive and significant effect on muzakki's trust.